Dulaglutide as an Add-on to Insulin in Type 2 Diabetes; Clinical Efficacy and Parameters Affecting the Response in Real-World Practice - Lee J (Dove Medical Press, 2019)
Jiwoo Lee, Yun Kyung Cho, Hwi Seung Kim, Chang Hee Jung, Joong-Yeol Park, Woo Je Lee Department of Internal Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of KoreaCorrespondence: Woo Je LeeDepartment of Internal Medicine, Asan Medical Center, University of Ulsan College of Medicine, 88, Olympic-Ro 43-Gil, Songpa-Gu, Seoul 05505, Republic of KoreaTel +82-2-3010-5882Fax +82-2-2045-4034Email lwjatlas@gmail.comPurpose: For patients with type 2 diabetes (T2DM) who remain above their glycemic target on insulin therapy, a combination of insulin and a glucagon-like peptide 1 receptor agonist has been recommended. However, few studies have been conducted to determine the clinical efficacy and parameters affecting the response to this combination in a real-world setting. This study aimed to investigate the clinical efficacy and parameters affecting the glycemic response to dulaglutide as an add-on to insulin therapy for T2DM in a real-world clinical setting.Patients and methods: A retrospective study was performed in 120 patients with T2DM who had initiated dulaglutide as an add-on to insulin therapy between January 2017 and December 2018. After 6 months of treatment, the change in glycated hemoglobin (HbA1c) was evaluated. Multiple linear regression analysis was used to determine the parameters affecting the therapeutic response to dulaglutide.Results: The mean age of the patients was 55.1 years and 57.5% were male. The mean baseline HbA1c, body mass index, and duration of diabetes were 9.1%, 27.5 kg/m2, and 17.2 years, respectively. The change in HbA1c between baseline and 6 months was −0.97% (95% confidence interval [CI]: −1.28 to −0.66%, P<0.001), the change in body weight was −2.05 kg (95% CI: −2.93 to −1.17 kg, P<0.001), and the change in total daily insulin dose was −11.67 IU (95% CI: −14.55 to −8.78 IU, P<0.001). In multiple linear regression analysis, higher baseline HbA1c was associated with a greater reduction in HbA1c. The most frequent adverse events were gastrointestinal symptoms, but these were well-tolerated.Conclusion: Dulaglutide treatment in combination with insulin resulted in a significant improvement in HbA1c and body weight over a 6-month period in a real-world clinical setting. Higher baseline HbA1c was associated with a good clinical response.Keywords: dulaglutide, glucagon-like peptide-1 receptor agonist, insulin therapy, glycemic control, diabetes mellitus